Moderasi Islam di Era Generasi Milenial - Anah, Saiul (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2022)
From the pesantren's womb figures were born who helped declarator and motorized the progress of the nation. However, in the recent development of boarding schools such as losing direction and identity in navigating the era of modernization. There are several traditions in the pesantren that are missing, such as intensive recitation of the sorogan and bandongan systems, which are proven to have produced reliable pesantren alumni who in the past were important elements in the pesantren system and curriculum. It should, when there is an effort to revitalize and optimize some of the important elements in the pesantren, the contribution of pesantren to the Indonesian nation will not be questioned anymore. This study aims to track pesantren religious thoughts and movements in the era of globalization. As well as describing the Islamic spirit of the santri in the pesantren environment which continues to be sought as a fortress for Muslims, In line with the millennial era, the faces of Islamic boarding schools in Indonesia are no longer monopolized by traditional groups or radicals, but have been colored by new pesantren formed by other Islamic groups with different faces.